Talectomy for the treatment of neglected pes equinovarus deformity in patients with neuromuscular involvement - (:unkn) unknown (My University, 2005)
OBJECTIVES: We evaluated talectomy operations performed for the correction of neglected pes equinovarus deformity of the foot in patients with neuromuscular involvement. METHODS: Eleven patients (2 females, 9 males; mean age 9.5 years; range 3 to 20 years) with various neurological disorders underwent 17 talectomy operations for the correction of neglected pes equinovarus deformity. Diagnoses were spina bifida in seven patients, arthrogryposis multiplex congenita in two patients, and spinal muscular atrophy and poliomyelitis in two patients, respectively. None of the patients had a previous surgery for pes equinovarus deformity. Preoperatively, three patients and one patient could walk in home settings with and without support, respectively, whereas seven patients could not walk at all. A protective orthosis was used in all the patients postoperatively. Achillotomy and posterior capsulotomy were performed prior to talectomy when needed. The results were evaluated with the use of a functional rating system and radiographs. The mean follow-up was 50 months (range 24 to 108 months). RESULTS: The results were good in 12 feet and fair in five feet. Seven patients could walk without support, and three patients could walk with support. One patient required re-operation for residual deformity of the foot and skin wounds due to poor compliance with the protective orthosis. One patient could not ambulate despite a plantigrade foot. CONCLUSION: Talectomy is a limb-saving procedure for the treatment of neglected pes equinovarus deformity. Its success relies not only on obtaining a plantigrade foot but also on a proper postoperative orthotic control.
Keywords: Adult; Female; Humans; Treatment Outcome; Adolescent; Male; Follow-Up Studies; Child; Child, Preschool; Radiography; Orthopedic Procedures; Neuromuscular Diseases; Orthotic Devices; Clubfoot; Talus